Exploring the potential of doped zero-dimensional cages for proton transfer in fuel cells: a computational study - Mane, Manoj V.; Venkatnathan, Arun; Ghatak, Kamalika; Vanka, Kumar (Journal of Physical Chemistry B, 2012)
Calculations with density functional theory (DFT) and MP2 have been done to investigate the potential of recently synthesized durable zero-dimensional (OD) nitrogen-based cage structures to perform as efficient proton-exchange membranes (PEMs) in fuel cells. Our calculations suggest that the hydrogenated 0-D cages, in combination with hydrogen-bonding 1,2,3- and 1,2,4-triazole molecules, would perform as highly efficient PEMs. The results are important in the context of the need for efficient PEMs for fuel cells, especially at higher temperatures (greater than 120 degrees C) where conventional water-based PEMs such as Nafion have been found to be ineffective.

Molecular dynamics simulation of phosphoric acid doped monomer of polybenzimidazole: a potential component polymer electrolyte membrane of fuel cell - Pahari, Swagata; Choudhury, Chandan Kumar; Pandey, Prithvi Raj; More, Minal; Venkatnathan, Arun; Roy, Sudip (Journal of Physical Chemistry B, 2012)
Phosphoric acid doped polybenzimidazole is promising electrolyte membranes for high temperature (100 degrees C and above) fuel cells. Proton conduction is governed by the amount of phosphoric acid content in the polymer membrane. In this present work, we perform molecular dynamics simulations on phosphoric acid doped 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole (monomer unit of polybenzimidazole) to characterize the structural and dynamical properties at varying phosphoric acid content and temperature. From the structural analysis, we have predicted the arrangement of the phosphoric acids, formation of H-bonds in the system, and the contribution of different atoms toward H-bonding. We have also examined the stacking of 2-phenyl-1H,1'H-5,5'-bibenzo[d]imidazole molecules and how their arrangement changes with the increasing amount of PA in the system with the help of cluster analysis. From the molecular dynamics simulation conducted at different temperatures and phosphoric acid doping level, we have predicted the diffusion of phosphoric acid and monomer. As a dynamic quantity, we have also calculated ring flipping of the imidazole ring of the monomer.

Characterization of the structures and dynamics of phosphoric acid doped benzimidazole mixtures: a molecular dynamics study - More, Minal; Pahari, Swagata; Roy, Sudip; Venkatnathan, Arun (Journal of Molecular Modeling, 2013)
Benzimidazole-based polymer membranes like poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are electrolytes that exhibit high proton conductivity in fuel cells at elevated temperatures. The benzimidazole (BI) moiety is an important constituent of these membranes, so the present work was performed in order to achieve a molecular understanding of the BI-PA interactions in the presence of varying levels of the PA dopant, using classical molecular dynamics (MD) simulations. The various hydrogen-bonding interactions, as characterized based on structural properties and hydrogen-bond lifetime calculations, show that both BI and PA molecules exhibit dual proton-acceptor/donor functionality. An examination of diffusion coefficients showed that the diffusion of BI decreases with increasing PA uptake, whereas the diffusion of PA slightly increases. The hydrogen-bond lifetime calculations pointed to the existence of competitive hydrogen bonding between various sites in BI and PA.
Keywords: Diffusion coefficient; Hydrogen bond; molecular dynamics; Radial distribution functions

Structure and dynamics of benzyl-NX3 (X = Me, Et) trifluoromethanesulfonate ionic liquids - Sunda, Anurag Prakash; Dhavale, Vishal M.; Kurungot, Sreekumar; Venkatnathan, Arun (Journal of Physical Chemistry B, 2014)
Ammonium-based benzyl-NX3 (X = methyl, ethyl) trifluoromethanesulfonate (TFA) ionic liquids (ILs) are low cost, nontoxic, thermally stable ion-conducting electrolytes in fuel cells and batteries. In the present study, we have characterized the structure and dynamics of these ILs using molecular dynamics (MD) simulations and ionic conductivity using electro-chemical impedance spectroscopy (EIS) at varying temperature and relative humidity (RH). Results from MD simulations predict that cation-cation and cation-anion interactions are stronger in benzyltrimethylammonium (BzTMA) compared to benzyltriethylammonium (BzTEA) that diminish with increase in RH. Further, the BzTMA cations show both C-H/Ph (center of mass of phenyl ring) and cation-Ph interactions whereas BzTEA cations show only strong cation-Ph interactions. The C-H/Ph interactions (psi >= 90 degrees, d(H-Ph) <= 4 angstrom, theta < 50 degrees and d(C.Ph) <= 4.3 angstrom) in BzTMA cations increase with RH and are highest at RH = 90%. The cumulative impact of electrostatic, cation/Ph, and C-H/Ph interactions results in lower conductivity of BzTMA-TFA IL compared to BzTEA-TFA IL. The EIS measurements show that the trends in ionic conductivity of ILs at RH = 30 and 90% are qualitatively similar to the Nernst-Einstein conductivity from MD simulations. The ionic conductivity of BzTEA-TFA IL is similar to 3 times higher than BzTMA-TFA IL at 353 K and RH = 90%.